Optimization of Steam Extraction Combined High Back Pressure Heating Based on Specific Consumption Theory - Zhanwei LIANG; Chenggang YANG; Lei ZHANG; Yatao XU; Peng SUN; Junjie ZHANG; Shunsen WANG (Zhongguo dianli)
With the wide application of new and high efficiency heating technology, it is becoming urgent to study the operation optimization of various heating technology combined heating. The simulation model of thermal power system is set up by using self-developed thermal power integration scheme (TPIS) software, together with the specific consumption analysis model established on the basis of exergy analysis method. The characteristics of heating specific consumption and power supply specific consumption varying with the load were studied. Then the optimal operating conditions of steam extraction combined high back pressure heating (mode one) and extracting steam cascade utilization combined high back pressure heating (mode two) are obtained by means of specific consumption analysis. Results show that the heating specific consumption and power supply specific consumption of mode two under the optimal condition are 1.6 kg/GJ and 4.6 g/(kW·h) lower than those of mode one, respectively. Mode one demonstrates higher heating capacity, which can supply heat within the range of 600 t/h to 1 000 t/h for main steam flow during secondary cold period. The research outcome can provide certain guidance for the operation optimization of steam extraction combined high back pressure heating.